Protein Losing Enteropathy After Cardiac Transplantation Successfully Treated by Stent Implantation. (November 2017) - Devanagondi, Rajiv; Suntharos, Patcharapong; Boyle, Gerard J.; Prieto, Lourdes R.
Protein losing enteropathy (PLE) is a severe consequence of Fontan physiology that sometimes requires heart transplantation for definitive treatment. We describe transplant refractory PLE in a patient with heterotaxia and complex systemic and hepatic venous connections, successfully treated by transcatheter relief of multiple venous obstructions.